Temperature-controlled optical switch metasurface with large local field enhancement based on FW-BIC - Wang, Xiuyu; Wang, Xiaoman; Ren, Qun; Cai, Haocheng; Xin, Jihong; Lang, Yuxin; Xiao, Xiaofei; Lan, Zhihao; You, Jianwei; Sha, Wei E. I. (Frontiers in Nanotechnology, 2023)
Many researchers have explored the bound states in the continuum (BICs) as a particular bound wave state which can be used to achieve a very high Q-factor. High-Q factor devices, typically based on the bound states in the continuum (BICs), are well used in the fields of hypersensitive biochemical sensors, nonlinear effects enhancement, plasmon lasers, and hi-performance filtering. However, symmetrical-protected BIC is difficult to achieve experimentally high-Q factor because it strongly depends on the geometry and can be destroyed by any slight disturbance in the potential well. Therefore, we proposed a parameter-adjusted Friedrich-Wintergen BIC based on the analysis model of time-coupled model theory, where the target system parameters can be tuned to achieve high-Q excitation. Moreover, considering the tunability and flexibility of the components in various practical applications, we integrate active materials into metasurface arrays with the help of external stimuli to achieve modulation of high-Q resonances. Our results demonstrate that an optical resonator based on FW-BIC can modulate the BIC state by changing the intermediate gap. The BIC state and the high-Q factor Fano resonance can be dynamically tuned by adding temperature-sensitive VO2 material.